Vouchers, choice, and public policy: An overview - Chumacero, Rómulo A.; Paredes, Ricardo D. (Estudios de Economía, 2012)
The educational voucher system builds on the pillars of informed choice and competition to improve the quality of the education provided. This document summarizes some of the results of recent literature on the subject, and discusses their public policy implications.